Reformes du marché de travail en Allemagne aucun effet sur lemploi et aggravation des déséquilibres en Europe - Camille Logeay; Katja Rietzler (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
– In this article an overview of the German macroeconomic performance in the last decade is stressed; extraordinary recovery of the German productivity and successes of the foreign trade face depressed domestic demand and a still worrying situation in the labour market. This article attempts to analyse the causes and consequences of these contradictory developments. Labour markets reforms in particular are focussed on in these lines. A macroeconomic evaluation of their impact on employment and wage developments is done and concludes that structural reforms cannot for themselves create more employment, they only can give a greater latitude for economic policy to boost demand without leaving the sustainable framework.
urn:nbn:de:101:1-20080818113
Keywords: E12; E50; 330; Germany; business cycle; unemployment; employment; Europe